2015
DOI: 10.1021/acsami.5b01100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exciton Localization on the Emission and Ultraviolet Photoresponse of ZnO/ZnS Core–Shell Nanowires

Abstract: The structural and optical properties of ZnO and ZnO/ZnS core-shell nanowires grown by a wet chemical method are investigated. The near-bandgap ultraviolet (UV) emission of the ZnO nanowires was enhanced by four times after coating with ZnS. The enhanced emission was attributed to surface passivation of the ZnO nanowires and localized states introduced during ZnS growth. The emission of the ZnO and ZnO/ZnS core-shell nanowires was attributed to neutral donor-bound excitons and localized excitons, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 50 publications
(92 reference statements)
4
28
0
Order By: Relevance
“…As shown in Figure 5B, the curves of FWHM show the "valley-shape" features that gradually disappear after thermal treatments. The "S-shape" and "valley-shape" characteristics obtained from the samples' emission have further confirmed the existence of localized states, which is consistent with previous reports [1,2,[6][7][8].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…As shown in Figure 5B, the curves of FWHM show the "valley-shape" features that gradually disappear after thermal treatments. The "S-shape" and "valley-shape" characteristics obtained from the samples' emission have further confirmed the existence of localized states, which is consistent with previous reports [1,2,[6][7][8].…”
Section: Resultssupporting
confidence: 91%
“…It has been confirmed that the localized effect can prevent the generated carriers from defusing to nonradioactive recombination centers, thus enhancing the emission and the response range of light. Therefore, at present, the localized states in the semiconductor nanomaterial have stimulated intensive research attention for high-performance excitonic optoelectronic devices, such as light-emitting diodes (LEDs), lasers, solar cells, and photodetectors [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,[19][20][21][22][23] Thus, various approaches such as quantum dots sensitization, introducing of localized surface plasmon or localized excitons have been adopted to optimize the performance of ZnO nanostructures. 21,[22][23][24][25][26] Herein, we propose the ZnS@ZnO core-shell nanowires/p-GaN structure heterojunctions. The strategy of using core/shell structure not only allows the efficient use of individual ZnO nanowires but also enhances the charge carrier recombination by localized excitons.…”
Section: Introductionmentioning
confidence: 99%